CORRELATIONS AMONG LEARNING STYLES, CLASSROOM ENVIRONMENT AND LISTENING COMPREHENSION - Destia D. Mulyani (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The aim of this study was to investigate the correlation among classroom environment, students’ learning styles, and their listening comprehension. Barsch’s learning style inventory, a classroom environment questionnaire, and a listening comprehension test were used to collect the data from 211 English Education Study Program students of Faculty of Teacher Training and Education, Sriwijaya University. The findings showed that most of the students were visual learners. In terms of classroom environment, they were at the high satisfactory of it. However, their listening comprehension result showed that most of them were in Poor category. The result of the correlational analysis showed that there was a significant correlation between the predictor variables (learning styles together with classroom environment) and the criterion variable (listening comprehension). Specifically, there were two aspects of listening comprehension (auditory and kinaesthetic learning styles) and two aspects of classroom environment (personalization and involvement) that had significant correlation with listening comprehension. These four aspects gave contribution 5.3% to the criterion variable.Keywords: learning styles, classroom environment, listening comprehension